Answer:
x=10/27
Step-by-step explanation:
just add the E's on one side than move over the other E than move 14 to the 4 by minusing it
Answer:
76
Step-by-step explanation:
recall that for a quadratic equation in the form
ax² + bx + c = 0, the discriminant is given by
discriminant, D = b²- 4ac
we are given the following:
-6x² + 2x + 3 = 0,
comparing this with the general equation above, it is clear that,
a = -6, b = 2 and c = 3,
substituting these into our equation for discriminant:
D = b²- 4ac
= 2² - 4(-6)(3)
= 4 + 72
= 76
Answer:
9. A. One - to - One Correspondence
10. D. None of the above
Answer:
A = ...-5π ,-4π ,-3π, -2π, -π, 0, π, 2π, 3π, 4π, 5π....
A = {x ∈ N, πx}
Answer:
C
Step-by-step explanation:
the correct answer is C